A scribe trained for the kingdom of heaven essays on Christology and ethics in honor of Richard B. Hays - Moffitt, David M. 1974-; Morales, Isaac Augustine 1976- (Lexington Books/Fortress Academic, 2021)
"This collection of exegetical and theological essays on the themes of New Testament Christology and ethics reflects the important contributions to those fields made by Richard B. Hays, in some cases building on and in other cases challenging his stimulating work"--
Keywords: Bibel -- Neues Testament; Bibelwissenschaft; Biblische Theologie; Jesus Christ / Person and offices / Biblical teaching; Christian ethics / Biblical teaching; Bible / Gospels / Criticism, interpretation, etc; Bible / Epistles of Paul / Criticism, interpretation, etc; Hays, Richard B. / honoree; Jesus Christ; Bible / Epistles of Paul; Bible / Gospels; Criticism, interpretation, etc; Festschrift